Modification of recombinant human epidermal growth factor (rh-EGF) expression vector by site-directed mutagenesis for therapeutic protein production - Achmad Rodiansyah; Riyona Desvy Pratiwi; Sabighoh Zanjabila; Asrul Muhamad Fuad (Indonesian Journal of Biotechnology, 2019)
Recombinant human epidermal growth factor (rh-EGF) has high value in therapies for h-EGF deficiency-related diseases. The expression of the h-EGF gene was designed by using the pET21b(+) vector and Escherichia coli BL21(DE3) as the expression host. In a previous study, the sequence of a 6xHis tag without any restriction sites was fused to the h-EGF gene, yet it was not possible to obtain a purified and single rh-EGF by this approach. In this study, we modified the rh-EGF expression vector using site-directed mutagenesis (SDM) to remove the sequence of the 6xHis tag. The vector modification was carried out by inserting a stop codon and the EcoRI restriction site, along with deleting the 6xHis tag sequence. The results of PCR showed non-specific bands, while 2-step cycles PCR produced one non-specific band, and 3-step cycles PCR produced two non-specific bands. After purification of the PCR products, the SDM-recombinant plasmids treated for template plasmid-free product were transformed into E. coli DH5a. Even though the transformation efficiency was low, the planned gene mutations including the deletion of the 6xHis tag and insertion of the stop codon and EcoRI restriction site in plasmid pET21b(+) were successfully carried out. When using this modified vector in expression studies, rh-EGF of a similar size to that of the rh-EGF standard and approximately 1 kDa smaller than the rh-EGF-6xHis of the previous study was obtained.